Masalah Penggunaan Ciptaan Sebagai Data Masukan Dalam Pengembangan Artificial Intelligence Di Indonesia - Gema, Ari Juliano (UI Scholars Hub, 2022)
The development of Artificial Intelligence (AI) is growing so fast. The availability of input data is important because it has a major impact on how the AI system will be developed. The use of copyrighted works as input data in AI development is also unavoidable. This paper tries to examine how the copyright law in Indonesia relates to the use of copyrighted works as input data for AI development. Based on the results of the study, it is known that the use of copyrighted works as input data for AI development in Indonesia still has to respect the exclusive rights of the creators to their works. A copyrighted work can be used as the input data without permission from its creator if it utilizes a work whose copyright protection validity period has expired and a work that uses an open license, and takes advantage of the provisions on copyright limitations and exceptions in the Indonesia's copyright law that allow the use of the copyrighted works without the permission of the creator with certain conditions. This paper provides suggestions that AI providers are treated as electronic system providers who are subject to registration obligations so that they can be required to disclose information when using copyrighted works as the input data, it is necessary to make a derivative regulation of Indonesia's copyright law which further explains the provisions on copyright limitations and exceptions, it is necessary to apply a non-exclusive license for mechanical rights (blanket license) thus simplify the licensing process for the use of copyrighted works as the input data for commercial and non-commercial purposes, the government needs to facilitate access to works whose copyright protection period has expired and works that use an open license, as well as to amend the Indonesia's copyright law to anticipate future AI developments.